Winter is for snow - Neubecker, Robert (New York : Disney*Hyperion, 2013)
"A brother and sister help each other learn to appreciate the joys of winter"--
Keywords: Stories in rhyme; Winter -- Fiction; Snow -- Fiction; Brothers and sisters -- Fiction; JUVENILE FICTION / Holidays & Celebrations / Christmas & Advent; JUVENILE FICTION / Concepts / Opposites; JUVENILE FICTION / Concepts / Senses & Sensation